2018
DOI: 10.1002/cae.21991
|View full text |Cite
|
Sign up to set email alerts
|

Exploring factors for effective use of online information in SPOC within the engineering education

Abstract: Today's Small Private Online Course (SPOC) environments are mashing different services from public, private, or hybrid clouds, different equipment, different tools, platforms, and learning pedagogies. The aim of this paper is to provide designers, developers, and educators with insights for implementation and utilization of such complex and heterogeneous SPOC frameworks. Factors that impact effective use of online information of designed digital content for engineering courses and successfulness of such system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…From Tables 1 and 2, it is observed that there are higher approval degrees for our online courses in the intensive undergraduate classes and the postgraduate class than for the regular undergraduate classes, which shows that the teaching materials are probably too difficult for regular undergraduate classes. Our results are consistent with Nejkovic's conclusion that SPOC platform quality is strong related to learners’ perceptions of the system and the perceived ease of use [23]. Consequently, we should design new teaching materials with a lower learning difficulty in the coming years for regular undergraduate classes (Table 3).…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…From Tables 1 and 2, it is observed that there are higher approval degrees for our online courses in the intensive undergraduate classes and the postgraduate class than for the regular undergraduate classes, which shows that the teaching materials are probably too difficult for regular undergraduate classes. Our results are consistent with Nejkovic's conclusion that SPOC platform quality is strong related to learners’ perceptions of the system and the perceived ease of use [23]. Consequently, we should design new teaching materials with a lower learning difficulty in the coming years for regular undergraduate classes (Table 3).…”
Section: Resultssupporting
confidence: 89%
“…The statistical data in Table 2 is similar to questionnaire surveys in the existing literature [6,23]. According to the statistical data, the majority of suggestions, respectively 73%, 96%, and 89.5%, can accept our online course mode.…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations